2012
DOI: 10.24036/jh.v11i1.625
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Keagamaan Mahasiswa Universitas Negeri Padang

Abstract: This research studied about students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This trend of ideological and religious understanding and attitudes toward Islam is also becoming popular among those newly engaged with religious discourse in college, especially in secular universities (Zein 2012). For those involved in the socialization of religious teachings such as halaqah (religious gathering), religion is understood as a social commitment to a better life; hence, it has ideological meaning.…”
Section: Religious Types and Narrativesmentioning
confidence: 99%
“…This trend of ideological and religious understanding and attitudes toward Islam is also becoming popular among those newly engaged with religious discourse in college, especially in secular universities (Zein 2012). For those involved in the socialization of religious teachings such as halaqah (religious gathering), religion is understood as a social commitment to a better life; hence, it has ideological meaning.…”
Section: Religious Types and Narrativesmentioning
confidence: 99%
“…Moreover, this Islamic fundamentalist thought has strengthened up and entered into the system of state universities. Various researches showed that public state universities in Indonesia such as UGM (Gadjah Mada University, ITB (Bandung Technological Institute), UI (the University of Indonesia), and other state universities in a rural area such as UNILA (Lampung University) of which type of religious activities are managed by a group of Islamic fundamentalist (Syarif & Mantu, 2018;Zein, 2012) encouraging dialogue between people of different religious beliefs, sharing spiritual experiences and engaging in religious pluralism. This approach is applied in a class that is attended by students whatever religious affiliations.…”
mentioning
confidence: 99%